Nonreassuring Fetal Status in the Second Stage of Labor: Fetal Monitoring Features and Association with Neonatal Outcomes - Triebwasser, Jourdan E.; Colvin, Ryan; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2016)
Objective To examine features of electronic fetal monitoring that prompt a diagnosis of nonreassuring fetal status (NRFS) and their association with acidemia.Study Design We identified all operative (cesarean or operative vaginal) deliveries from a retrospective cohort study of term singletons delivered in the second stage. The primary exposure was indication for delivery, NRFS versus other. We compared fetal monitoring features in the 30 minutes prior to delivery. In those delivered for NRFS, we assessed features associated with acidemia (pH < 7.2). Logistic regression adjusted for confounders.Results Of 5,388 patients, 770 (14%) were delivered operatively. NRFS (77%) was associated with acidemia (adjusted odds ratio 3.7, 95% confidence interval 2.1–6.5). Total deceleration area, repetitive late decelerations, and marked variability were associated with NRFS. However, only number of prolonged decelerations and total deceleration area were associated with acidemia in the NRFS group.Conclusion The majority of deliveries for NRFS and the features that prompt that diagnosis are not associated with acidemia.
Keywords: nonreassuring fetal status; indication; operative delivery; fetal monitoring; second stage